Number of episodes and duration of illness associated with hypertension and 10-year cardiovascular risk in patients with bipolar disorder type I. (February 2022) - Aguglia, Andrea; Salvi, Virginio; Amerio, Andrea; Gari, Matteo; Dragogna, Filippo; Mencacci, Claudio; Volpe, Umberto; Serafini, Gianluca; Amore, Mario
Highlights: Severe mental Illnesses, as bipolar disorder and schizophrenia, showed an increased cardiovascular risk. Patients with bipolar disorder type I presented higher prevalence of hypertension and 10-year cardiovascular risk. The diagnosis of hypertension and 10-year cardiovascular risk are correlated with number of episodes and duration of illness. Abstract: Severe Mental Illnesses, including bipolar disorder (BD) and schizophrenia (SCZ), are burdened with an increased mortality and a significantly reduced life expectancy than general population, and cardiovascular diseases (CVD) are considered the most contributing conditions. The aim of the present study is to evaluate 10-year CV risk and the associated clinical characteristics in patients with SCZ, BD type I and II. Patients were consecutively recruited from two Italian psychiatric acute units. Single CV risk factors were assessed, and 10-year CV risk calculated by means of the CUORE Project 10-year CV risk algorithm, based on the combination of the following risk factors: age, systolic blood pressure, total and high-density lipoprotein cholesterol, diabetes, smoking habit, and hypertensive treatment. Three hundred patients were included. Patients with BD type I showed a higher prevalence of hypertension and 10-year CV risk score compared to the other groups. In subjects with BD type I, we found a significant correlation between duration of illness and number of mood episodes and both hypertension and 10-year CV risk score. Several preventive strategies should be provided to these vulnerable populations, such as correcting unhealthy lifestyles, prescribing medications at lower CV and metabolic risk, enhancing access to care.